Complexity and Adaptive System of Television Broadcasting: The Reﬂection of Autopoetic Mechanism of Indonesian Television Broadcasting System - Hermin Indah Wahyuni (Jurnal Ilmu Sosial dan Ilmu Politik, 2017)
This article aims to describe a model of a robust adaptive system which suits the context of situation in Indonesian as an archipelago, as well as developing and democratic values-based country. It mainly focuses on how the autopoetic mechanism in Indonesian television broadcasting system is. Autopoetic mechanism is self-reference orientation. The process in which the system orient to reduce their problem by building the internal structure to cope with it. The research process was done in 2014 until 2016. Methods applied in this research is qualitative research. Several methods that were employed are observation, in-depth interview, and focus group discussion. It would be measured and analysed with three aspects: communication, temporal and diﬀerentiation aspect. The ﬁndings suggest that building a robust system means establishing a “strong and adaptive” broadcasting system in Indonesia that strengthens each sub-system in the Indonesian broadcasting system in order to capture what the public demands. In this level it takes a comprehensive view of the decision-makers to design a broadcasting system that continues to answer the demanding environment through its communication function, growing temporal through continuous evolution and develop functions through a process of diﬀerentiation. If these three functions can work continuously, Indonesian broadcasting system will be stronger and more adaptive with their complex external environment. The main argument of this paper is Indonesian Broadcasting System faces a very complex environment television, however their adaptive and autopoetic mechanism is still weak to cope with the challenges.